Coronary Computed Angiography and Coronary Artery Calcium Score for Preoperative Cardiovascular Risk Stratification in Patients Undergoing Noncardiac Surgery - Ioannis Kyriakoulis; Sriram S. Kumar; Georgios D. Lianos; Dimitrios Schizas; Damianos G. Kokkinidis (Journal of Cardiovascular Development and Disease)
Perioperative and long-term postoperative major adverse cardiovascular events (MACE) are a leading cause of morbidity and mortality in patients undergoing noncardiac surgery. In selected high-risk patients, when information about cardiovascular status may influence surgical decisions, preoperative risk stratification is reasonable, with stress imaging being the preferred method. Coronary computed angiography (CCTA) and coronary artery calcium score (CACS) offer direct anatomical assessment of atherosclerotic coronary arteries and help gauge the extent and severity of coronary artery disease. Strong evidence supports that CCTA and CACS, either alone or in combination, are reliable methods for assessing the risk of both perioperative and long-term postoperative MACE, often demonstrating equal or superior prognostic performance compared to traditional imaging tools. Moreover, integrating CCTA or CACS into standard preoperative imaging protocols further enhances perioperative risk prediction and improves the ability to accurately stratify patients. Future research is needed to better define the role of CCTA and CACS in preoperative cardiovascular risk evaluation of patients undergoing noncardiac surgery.